Ketidakpastian Hukum Lembaga Jaminan Fidusia dalam Perspektif Kreditur yang Beritikad Baik di Indonesia - Umami, Allan Mustafa; Aryadi Almau Dudy (PT Satya Pertama Nusantara, 2024)
Security Institution is a means to provide legal protection for creditors in order to obtain debt repayment from debtors. Fiduciary Guarantee is a material guarantee in the form of movable and immovable objects that are not included in the objects of Mortgage and Mortgage. Fiduciary guarantees are characterised by the transfer of ownership rights from the fiduciary grantor to the fiduciary recipient. The control of the object of fiduciary guarantee is vested in the fiduciary. Law No. 42/1999 on Fiduciary Guarantee grants preferential rights. The fiduciary beneficiary also has the right to execute the object of the fiduciary guarantee if the debtor defaults. Starting from the Decision of the Constitutional Court (MK) Number 18/PUU-XVII/2019 which interprets Article 15 of Law Number 42 of 1999 that if the debtor defaults, the creditor has no right without a court decision to execute the object of fiduciary security. The problem in this research is what causes legal uncertainty of fiduciary security institutions in Indonesia in the perspective of good faith creditors? The result of this research is the cause of legal uncertainty is the implementation in the field is not in accordance with Law Number 42 Year 1999. The decision of the Constitutional Court (MK) Number 18 / PUU-XVII / 2019 further complicates good faith creditors to obtain rights in the form of returning their debts from debtors.